Singing peace and forgiveness: The case of Jah Prayzah, Sulumani Chimbetu, Chiwoniso Maraire and Edith Weutonga - Rwafa, Urther (Taylor & Francis (Routledge), 2016)
The album Moyo Munyoro (2013) is a product of a collaborative effort in which four Zimbabwean musicians, Jah Prayzah, Sulumani Chimbetu, Edith Weutonga and the late Chioniso Maraire combined skill and commitment to sing about peace, forgiveness and development in Zimbabwe. The July 31st elections of 2013 have come and gone. Yet before the elections, there was a general anxiety and fear among Zimbabweans that the July 31st elections would simply replay the template of political violence that marred the 2008 harmonised presidential elections. The aim of this article is to explore Moyo Munyoro (2013) in order to find how, through its varied songs, the album has helped to spread the “gospel” on peace, forgiveness and development among Zimbabweans. This was mainly a response to the commitment and maturity demonstrated by both ZANU PF and MDC politicians who preached about peace during most of their political campaigns as the country moved towards 2013 general elections. This article is going to argue that it is important for musicians to echo and question politicians’ discourses on matters regarding peace building in Zimbabwe, and yet one can get the impression that Zimbabwean musicians rarely sing about the need for peace to prevail unless that discourse is started and popularized by politicians. The idea of “automatically” and “uncritically” responding to meta narratives on peace and forgiveness cascading from government officials creates aporia between the discourses that tap from “top-down” or “elitist” approaches to peace building against those discourses that support “grass-roots and participatory” methodologies that stress the idea that peace building and forgiveness should start with members of the community bearing the scars and memories of political violence. This demonstrates that Zimbabwean musicians are part of the “grass-roots” communities who should not wait for violence to occur so that they sing about peace or play second fiddle to politicians in condemning acts of political violence.